The Positive Effect of Workplace Accommodation on Creative Performance of Employees With and Without Disabilities - Man, Xiangyu; Zhu, Xiji; Sun, Cong (Frontiers in Psychology, 2020)
The issue of workplace accommodation is vital to employees with and without disabilities, as well as employers and organizations. Drawing on the self-efficacy theory, this paper examines the mechanism and contingency of the relationship between workplace accommodation and employee creative performance. Specifically, we argue that creative self-efficacy is the key factor through which workplace accommodation promotes employee creative performance. Aligning with the identity-blind diversity management, we hold a continuous view of disability that everyone has a certain level of disability ranging from zero to a high level of disability severity. Disability severity moderates the relationship between workplace accommodation and creative self-efficacy, and the aforementioned indirect effect, such that the positive relationship and the indirect effect are stronger for employees with a lower level of disability severity. Data collected from a multi-wave multi-source field study with 300 participants provides general support for our hypotheses. This research contributes to the literature by a) providing empirical support for the identity-blind diversity management, b) extending the research on the psychological well-being and performance of employees with disabilities, and c) enlarging the nomological network of workplace creativity. Practically, our research provides insights for practitioners to promote workplace accommodation practices, as workplace accommodation is not only essential for including employees with disabilities but also helpful in boosting the creative performance of all employees.